Ceragenins – a new weapon to fight multidrug resistant bacterial infections - Surel, Urszula; Niemirowicz, Katarzyna; Marzec, Michal; Savage, Paul B.; Bucki, Robert (Medical Studies/Studia Medyczne, 2014)
Growing antibiotic resistance among pathogenic microorganisms is one of the most challenging problems. Often, a single mutation in a bacterial cell leads to the formation of a new drug resistance mechanism. The ceragenins are a novel class of antibiotic, offering great promise in future treatment of infections. These cationic antimicrobial lipids are net positively charged cholic acid derivates that are electrostatically attracted to the negatively charged membranes of bacteria, certain viruses, fungi, and protozoa. After membrane insertion, they interfere with membrane organisation, resulting in membrane dysfunction and cell death. This review focuses on the broad spectrum of antibacterial activity of ceragenins, and their potential to become a new group of antibiotics for prevention and treatment of infections, especially those caused by multidrug-resistant bacteria.